Angewandte Linguistik - Neue Herausforderungen und Konzepte (Edition 1) - Lisek, Grzegorz (2021)
In 24 theoretischen und praxisbezogenen Beiträgen nähern sich Wissenschaftlerinnen und Wissenschaftler aus Deutschland, Österreich und Polen den aktuellen Problemen aus dem weit verstandenen Gebiet der angewandten Linguistik an. Die Beiträge stammen aus den folgenden thematischen Gebieten: Pragma- und Soziolinguistikstudien, kontrastive Studien, Interkulturalität, Spracherwerbs- und Sprachlehrforschung, Fachsprachen, Übersetzen und Dolmetschen sowie Lingustic Landscapes. Der vorliegende Band greift damit die vielseitigen Forschungsinteressen von Prof. Dr. habil. Izabela Prokop auf, die im Jahr 2021 ihr 70. Lebensjahr vollendet. The present book is a collection of 24 theoretical and empirical contributions which approach current problems within a widely understood field of applied linguistics. Their authors come from Germany, Austria and Poland and represent major academic institutions in these countries. The chapters included in the monograph treat about the most recent issues in the field and are organized into seven thematic foci: Pragma- and sociolinguistics, contrastive studies, interculturality, language acquisition and language teaching research, specialised languages, translation and translation studies, and research in linguistic landscape. The incentive for putting this monograph together is the 70th birthday of prof. Izabela Prokop.